Banking efficiency in Asian: A stochastic frontier analysise - Thi Nguyen, Thu (2008)
Banking sector plays an important role in financial system of a nation. It is essential to ensure that banks are performing under efficient manor and to measure productive efficiency of banks as a basis for implication toward government policy, corporate governance and other managerial issues. Stochastic frontier analysis is essentially a sophisticated way to measure technical efficiency of banks.